2006
DOI: 10.1111/j.1469-0691.2006.01398.x
|View full text |Cite
|
Sign up to set email alerts
|

Current challenges in the treatment of complicated urinary tract infections and prostatitis

Abstract: Serious urinary tract infections (UTIs) and acute bacterial prostatitis in adults cause significant morbidity and economic burden. Chronic bacterial prostatitis is a rather rare condition seen in urological practice, however, in certain occasions difficult to treat. In this paper, we review the bacterial etiologies and the resistance patterns found in adults with serious UTIs and bacterial prostatitis, and discuss considerations for selecting optimal antimicrobial therapy. The role of fluoroquinolones as targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 93 publications
1
40
0
6
Order By: Relevance
“…That is, our observations confirm clinical findings that Ps. aeruginosa is particularly damaging to prostate tissue (Wagenlehner & Naber, 2006). Indeed, in this study, a new tissue-grading scale was developed to account for the increased damage observed in Ps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, our observations confirm clinical findings that Ps. aeruginosa is particularly damaging to prostate tissue (Wagenlehner & Naber, 2006). Indeed, in this study, a new tissue-grading scale was developed to account for the increased damage observed in Ps.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa in the prostate deserves attention due to the fact that clinical reports indicate that Ps. aeruginosa prostatitis is difficult to treat and exceptionally damaging to prostate tissue (Nickel & Costerton, 1993;Wagenlehner & Naber, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Azithromycin was administered only during the first 3 consecutive days at the beginning of each week of treatment with the fluoroquinolone (''pulse therapy''), as previously described. 18,28,29 In agreement with the algorithm recommended by Wagenlehner and Naber, 30 patients remained on continuous treatment with the alphaadrenoceptor blocker alfuzosin ER (10 mg day 21 ) for a period of 6 months, during which time a supplement containing Serenoa repens extract (640 mg day 21 ), lycopene (5 mg day 21 ) and selenium (50 mg day 21 ) in a single formulation was also administered. 31 Four weeks after the end of antimicrobial treatment, the patients were subjected to a complete diagnostic protocol, including microbiological and clinical evaluations.…”
Section: Diagnostic Proceduresmentioning
confidence: 93%
“…6 The remaining cases are associated with a variety of organisms, including the Gram positive bacteria like Enterococcus, Staphylococcus especially coagulase negative staphylococci, Streptococcus agalactiae and other less frequently isolated organisms. 7 However, Gram positive bacteria are found more often as etiologic agents in vulnerable groups such as pregnant women and the elderly. Complicated UTI is defined as cystitis or pyelonephritis that occurs in individuals with predisposing anatomic, metabolic or functional risk factors making their treatment difficult.…”
Section: Introductionmentioning
confidence: 99%